INTEGRATING INFORMATION TECHNOLOGIES IN ENGLISH LANGUAGE TEACHING: FOSTERING STUDENTS’ DIGITAL LITERACY SKILLS - Akhmadova, Feruza (International Conference on Science, Education & Law, 2025)
This study examines the role of English language teachers in developing students’ digital literacy through the integration of information and communication technologies (ICT). It highlights how modern pedagogical and psychological approaches can be enhanced by digital tools to foster critical thinking, creativity, and independent learning. The research combines theoretical and practical methods, including comparative analysis and classroom observation, to evaluate the effectiveness of ICT integration in English language teaching.